Interdisiplin: Proses Pembelajaran Di Padhepokan Seni Mangun Dharma Kecamatan Tumpang Kabupaten Malang - Gesti Manggarrani Pratiwi; Setyo Yanuartuti (Gondang: Jurnal Seni dan Budaya, 2020)
Padhepokan Seni Mangun Dharma is a traditional art studio in Malang Regency. The art taught in this studio is Malang Puppet Mask, kerawitan, dance, pedhdalang, mocopatan. Padhepokan environment that is still fresh and beautiful has always been the basis of the approach in the learning process. The purpose of this paper is to study the nature-based learning process in Padhepokan Mangun Dharma with an interdisciplinary approach. The research method used is descriptive qualitative. Learning with character-based nature is what can be applied to the learning of art in the hospices of Mangun Dharma. Open nature such as in mountain areas, rice fields, rivers around the studio is an excellent ecology to teach children art now. With a free, fresh nature can increase children's focus in learning. The concept of the Maharsi Begawan Pandhito concept is an approach in learning ecology-based arts. Such learning is carried out because in order for the cantrik and mentrik to get to know nature because nature is a source of humanity to explore, create, and express.